Effects of Shop Size and Labor Flexibility in Labor and Machine Limited Production Systems - Fryer, John S. (Management Science, 1975)
This paper describes a simulation study that examines the influence of system size and labor flexibility on the performance effects of dispatching and labor control decision rules in labor and machine limited production systems. Four production systems are used—a small job shop, a medium job shop, a large job shop in which workers may be transferred between major organizational divisions, and a large job shop in which workers cannot be transferred between divisions. For each system the decision rules for dispatching and labor control are varied. Comparisons are made of the relative effects of the decision rules, for the different systems, on mean flow-time, flow-time variance and number of worker transfers. Results indicate that the effects of dispatching and labor control decision rules on flow-time measures are consistent for different size and labor flexibility combinations. With one exception, the effects on labor transfer measures are also consistent. Consistency here means that the directions of change in performance measures are the same for the different systems. The magnitudes of both actual and percentage changes do vary for the different systems.